2012
DOI: 10.1074/jbc.m111.305441
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Role for Dematin in Regulating Red Cell Membrane Function by Modulating Spectrin-Actin Interaction

Abstract: Background:The role of dematin in regulating red cell membrane mechanical function is not well understood. Results: Dematin facilitates spectrin-actin interaction, and this activity is modulated by PKA phosphorylation of dematin. Conclusion: Dematin binds to spectrin and dynamically regulates red cell membrane mechanical function. Significance: A novel role for dematin in regulating red cell membrane mechanical function has been unraveled.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 26 publications
0
49
0
Order By: Relevance
“…50 For instance, the phosphorylation of cytoskeletal proteins by PKA or other kinases decreases the membrane stability. [51][52][53] We propose that PKA-mediated phosphorylation of STEVOR S 324 may change the conformation of the STEVOR C-terminal domain and increase its interaction with the skeleton partner, thus increasing stiffness of the membrane. These interactions are also likely dependent on phosphorylation or other posttranslational modifications of host membrane proteins.…”
Section: Discussionmentioning
confidence: 99%
“…50 For instance, the phosphorylation of cytoskeletal proteins by PKA or other kinases decreases the membrane stability. [51][52][53] We propose that PKA-mediated phosphorylation of STEVOR S 324 may change the conformation of the STEVOR C-terminal domain and increase its interaction with the skeleton partner, thus increasing stiffness of the membrane. These interactions are also likely dependent on phosphorylation or other posttranslational modifications of host membrane proteins.…”
Section: Discussionmentioning
confidence: 99%
“…35 These studies suggested a functional role of dematin in late erythropoiesis, consistent with earlier studies on dematin expression during erythropoiesis. 26,36 Our results show that dematin functions as a negative regulator of erythroblast enucleation without affecting primitive erythropoiesis (Figure 2). This finding is consistent with the absence of nucleated erythroid precursors in the peripheral blood of FKLO mice.…”
Section: Discussionmentioning
confidence: 79%
“…This finding is consistent with a previous demonstration that dematin binds to a mini-spectrin construct containing both a and b subunits, and this interaction is sensitive to phosphorylation of dematin by cAMP-dependent protein kinase. 26 As mentioned in the previous study, 26 the biochemical interaction of dematin with actin and spectrin and its sensitivity to phosphorylation by cAMPdependent protein kinase have been previously documented. 4,17 In our study, we also noticed a significant reduction in the protein-protein interaction between spectrin and the full-length dematin-S381E mutation ( Figure 5F,G, lane 11).…”
Section: Dematin Is Essential For Rbc Membrane Integrity 97mentioning
confidence: 72%
“…These differences make non-erythrocytic spectrin more stable and erythrocyte spectrin more flexible. Except for the resolved spectrin repeat fragments, the crystal and NMR structures of the domains interacting with other proteins have also been resolved, including actin-binding [19] and pleckstrin homology domains [20] (Table 2). …”
Section: The Structure Of Spectrinmentioning
confidence: 99%